Oral Health by Using Probiotic Products 2019
DOI: 10.5772/intechopen.86762
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of Probiotics and Prebiotics

Abstract: Advancement in technology is continued as the time is passed. The biological active ingredients technology is the challenging issues for both the researchers and manufacturers. In last decade, much research has been happened about the potential health benefits of pro and prebiotic ingredients. Probiotics are the live microorganisms when given in adequate amount confer health benefits but the prebiotics are indigestible ingredients that enhance the activity of one or more probiotics in the colon. The therapeuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 115 publications
(107 reference statements)
0
7
0
Order By: Relevance
“…Probiotics are drinks containing probiotic bacteria which has health effects due to the fermentation process. Probiotics can be used as antihypercholesterolemia therapy since probiotic bacteria can increase the secretion of Bile Salt Hydrolase (BSH) enzyme which then enable the increasing excretion of bile acids (Naim, 2011;Gulzar et al, 2019). Apart from that, probiotic bacteria produce cholesterol dehydrogenase cofactor which functions to activate the cholesterol reductase enzyme, converting cholesterol into cosprotanol.…”
Section: Introductionmentioning
confidence: 99%
“…Probiotics are drinks containing probiotic bacteria which has health effects due to the fermentation process. Probiotics can be used as antihypercholesterolemia therapy since probiotic bacteria can increase the secretion of Bile Salt Hydrolase (BSH) enzyme which then enable the increasing excretion of bile acids (Naim, 2011;Gulzar et al, 2019). Apart from that, probiotic bacteria produce cholesterol dehydrogenase cofactor which functions to activate the cholesterol reductase enzyme, converting cholesterol into cosprotanol.…”
Section: Introductionmentioning
confidence: 99%
“…9,18 Probiotics, prebiotics, and synbiotics are therefore studied to enhance human health. [7][8][9] 2.2. Colorectal cancer CRC ranks the third in the prevalence of most common cancers, 20 and the probability of suffering this cancer is about 4%-5%.…”
Section: Inflammatory Bowel Diseasesmentioning
confidence: 99%
“…6 GM can be manipulated by supplementing live beneficial microorganisms, i.e., probiotics, compounds facilitating the growth and activity of probiotics, i.e., prebiotics, or ''a mixture comprising live microorganisms and substrate(s) selectively utilized by host microorganisms that confers a health benefit on the host,'' i.e., synbiotics. [7][8][9] Dietary fibres are not digestible in the gastrointestinal (GI) tract and not directly bioactive. 3 However, dietary fibres, especially soluble ones, can be fermented by GM in the colon, and the metabolites contribute to gut health.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in Crohn’s disease (CD), a type of IBD, it was evaluated that the incidence of a misbalance in gut microbiota was high when F. prausnitzii was observed [ 237 ]. Prebiotics have been used to control the adverse effects in CD patients [ 238 ]. A study reported a decline in the number of Bacteroides in the fecal matter of CD patients when they received inulin at 24 g/day [ 239 ].…”
Section: Health Benefits Of Prebioticsmentioning
confidence: 99%